1977
DOI: 10.1159/000169865
|View full text |Cite
|
Sign up to set email alerts
|

On the Frequency of Early Systolic Clicks in Mitral Valve Prolapse

Abstract: Phonocardiography was performed in 74 patients with mitral valve prolapse. 24 patients had early systolic clicks ( < 80 msec from S1). Four of them had associated systolic murmurs. 30 patients had mid or late systolic clicks ( > 80 msec from S1). A systolic murmur followed the click in 13 of these patients. Both an early and mid/late systolic click were noted in three patients. 17 patients did not have systolic clicks. Eight of these patients had holosystolic murmurs and two had late syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Other types are classified as sporadic nonsyndromic MVP [10], [11]. A floppy mitral valve plays a pivotal role in the pathogenesis of MVP [12], [13] The associate editor coordinating the review of this manuscript and approving it for publication was Behrouz Shabestari.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other types are classified as sporadic nonsyndromic MVP [10], [11]. A floppy mitral valve plays a pivotal role in the pathogenesis of MVP [12], [13] The associate editor coordinating the review of this manuscript and approving it for publication was Behrouz Shabestari.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Framingham Heart Study reported that MVP was associated with a low incidence of complications in the general population [1], many case studies have revealed that those with MVP have a higher risk of bacterial endocarditis [14], [15], ischemic stroke [16], severe mitral regurgitation [2], [4], [17], and complicated ventricular arrhythmias [18], [19]. As early as 30 years of age or older, the presence of a mitral systolic click can be physically auscultated in 10-20% of patients with MVP [12], [13], depending on the severity of the MVP and the mitral regurgitation [13]. Early screening of MVP in young adults is crucial for confirmation by echocardiography, which may facilitate a decision making made by primary physicians in specific clinical situations, e.g., antibiotic prophylaxis during surgery to prevent the occurrence of bacterial endocarditis related to MVP [20].…”
Section: Introductionmentioning
confidence: 99%
“…A floppy mitral valve plays a pivotal role in the pathogenesis of MVP 11 and can be assessed by imaging and physical examinations. Systolic click in cardiac auscultation is a typical finding for floppy mitral valve, and the prevalence is estimated from 10 to 70% in patients with MVP 1,12 . A specific heart sound has emerged in patients after 30 years of age, and the intensity increases with more severe MVP and decreases with a higher grade of mitral regurgitation 11,13 .…”
mentioning
confidence: 99%